Analgesic action of adenosine A1 receptor involves the dephosphorylation of glycine receptor α1ins subunit in spinal dorsal horn of mice. (1st October 2020) - Diao, Xin-Tong; Yao, Lin; Ma, Juan-Juan; Zhang, Tian-Yu; Bai, Hu-Hu; Suo, Zhan-Wei; Yang, Xian; Hu, Xiao-Dong
Abstract: Glycine receptor α1 ins subunit is located at inhibitory synapses in the superficial dorsal horn of adult spinal cord and is engaged in the glycinergic inhibition of nociceptive neuronal excitability and transmission. The α1 ins phosphorylation at Ser380 by extracellular signal-regulated kinase (ERK) has been shown to decrease glycinergic synaptic currents and contribute to spinal disinhibition. Here we found that peripheral inflammation induced by Complete Freund's Adjuvant increased Ser380 phosphorylation in spinal cord dorsal horn of mice, which was repressed by specific activation of adenosine A1 receptor (A1R). Protein phosphatase-1 (PP1), a ubiquitously-distributed serine/threonine phosphatase, was required for A1R to reduce Ser380 phosphorylation. Our data showed that Gβγ dimer, when released after activation of Gi protein-coupled A1R, interacted with PP1 and directed this phosphatase to α1 ins, allowing for the full dephosphorylation of Ser380 residue. Sequestration of Gβγ dimer by viral expression of the C-terminal tail of β-adrenergic receptor kinase (βARKct) dissociated PP1 from α1 ins complex, leading to robust Ser380 phosphorylation. Meanwhile, Gβγ inhibition compromised the ability of A1R to alleviate inflammatory pain. The inhibitory effect of A1R on Ser380 phosphorylation was also attributed to the inactivation of ERK in CFA mice. Our data thus identified glycine receptor α1 ins subunit as an important target for adenosinergic suppression of inflammatory pain. Highlights: Specific activation of A1R reduced Ser380 phosphorylation on GlyRs α1 ins subunit. PP1 mediated Ser380 dephosphorylation. Gβγ dimer directed PP1 to α1 ins for Ser380 dephosphorylation after A1R activation. α1 ins was one of the targets for adenosinergic suppression of inflammatory pain.